2020
DOI: 10.17508/cjfst.2020.12.1.06
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of cooking methods on the nutritional properties and quality attributes of meat from various animal sources

Abstract: This study investigated the various effects of two food product processing methods (boiling and grilling) on the nutritional composition (fatty acid, amino acid profiles) of meat from cows, goats, and rabbits. Freshly slaughtered animals were cleaned and subjected to boiling and grilling. Cooking loss varied with cooking methods; grilling resulted in the highest cooking loss, especially in cow meat (52.95%). Data from the proximate composition analysis revealed that both raw and grilled meat samples of rabbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…Boiling pork meat at 60 and 75 • C decreased the protein content by 11% and 18%, respectively, compared to raw meat; histidine was the most affected amino acid, showing reductions of 17% and 31%, respectively [84]. Olagunju and Nwachukwu [83] found no differences in total and in essential amino acids of goat meat grilled or boiled compared to raw meat. Meanwhile, these authors found that heating significantly affected the amino acid content of cow meat with a decrease of tyrosine > tryptophan > glycine in meat boiled or grilled compared to raw meat.…”
Section: Proteinsmentioning
confidence: 88%
See 2 more Smart Citations
“…Boiling pork meat at 60 and 75 • C decreased the protein content by 11% and 18%, respectively, compared to raw meat; histidine was the most affected amino acid, showing reductions of 17% and 31%, respectively [84]. Olagunju and Nwachukwu [83] found no differences in total and in essential amino acids of goat meat grilled or boiled compared to raw meat. Meanwhile, these authors found that heating significantly affected the amino acid content of cow meat with a decrease of tyrosine > tryptophan > glycine in meat boiled or grilled compared to raw meat.…”
Section: Proteinsmentioning
confidence: 88%
“…Table 3 summarizes the effect of the heating process on the nutritional value (fatty acids, proteins, vitamins, and minerals) of meat from different animal species described in the following sections. Total lipids, SFA and MUFA increase, PUFA decrease [73] Total lipids, SFA and MUFA increase, PUFA decrease [73] Total lipid increase, SFA increase [74] Total lipids increase in Limousin calves [75] Protein digestibility decrease [76] Leucine, glutamic and aspartic acid increase [77] Protein digestibility increase [76] Leucine, glutamic and aspartic acid increase [77] Protein digestibility increase [76] Vitamin E decrease [75] No effect on vitamin B12 [78] No effect on vitamin B12 [78] Vitamin B1 and vitamin D decrease [79] Vitamin D decrease; vitamin B12 decrease [78] Vitamin E decreases [75] Ash increase from 1 to 1.3% [72] Na, K, P, Ca and Mg decrease Fe and Zn increase [79] Na, K, P, Ca and Mg decrease, while Fe and Zn increase [79] Fe, Mg and K decrease [80] Ca, Cu, Fe, K, Mg decrease in bovine liver [81] Ca, Cu, Fe, K, Mg stability in bovine liver [81] Sheep and Goat SFA, MUFA and PUFA increase [82] Ash increase [83] SFA, MUFA and PUFA increase [82] Ash increase [83] No differences in total amino acids and in essential amino acids [83] No differences in total amino acids and in essential amino acids [83] Pig Total lipids and ash increase [81] Total amino acids content decrease [84] Tryptophan decrease [85] Protein digestibility increase [86] Vitamin B1 strong decrease [79] Protein digestibility increase [87] Ash increase [72]; Na, K, P, Ca and Mg ...…”
Section: Effect Of Heating Processes On Meat Nutritional Valuementioning
confidence: 99%
See 1 more Smart Citation
“…b. Crude Fat Content: Determined by saponifying the extracted fat content of the sample and then analyzed by gas chromatography described by Olagunju and Nwachukwu, (2019). c. Protein Content: Measured by the micro-Kjeldahl method, where the percentage nitrogen content was calculated and multiplied by a factor of 6.25 to determine the protein content (Equation 2).…”
Section: Methodsmentioning
confidence: 99%
“…It is suspected that there is a process of leaching nitrogenous compounds into the boiling water because the protein dissolves easily in water. (Olagunju & Nwachukwu 2020). Also, boiling and grilling may reduce protein content in meat due to protein denaturation.…”
Section: Chemical Analysismentioning
confidence: 99%